Inventory of land snails from Boquerones, Ciego de Avila, Cuba - Pereira-Miller, Félix Jonathan (2015)
A census of mollusks in Boquerones, Ciego de Avila, Cuba was carried out. Biodiversity index were studied by vegetal formation, which are: Evergreen Forest, Semideciduous Forest and Mogote Vegetation Complex. The families best represented were Helicinidae, Annularidae, Urocoptidae and Subulinidae, taking the 97.6% of the species some degree of national endemism and being the 45.24% of these local endemic. The most widely distributed species was Farcimen camaguayanum Torre & Bartsch 1941 and the rarest was Euclastaria euclasta Shuttleworth 1852. The highest biodiversity values were observed in the Mogote Vegetation Complex being of 2,856 according to Shannon-Wiener (H´) index. So far species extinction events are not seen but not discarded for the future due to a decline in local rainfall during the last 15 years as well as human activities such as agriculture and local tourism.